Acute Skin Failure in the Critical Care Patient. (April 2020) - Delmore, Barbara; Cox, Jill; Smith, Daniel; Chu, Andy S.; Rolnitzky, Linda
ABSTRACT: OBJECTIVE: The purpose of this research was to build on previous work regarding predictive factors of acute skin failure (ASF) in the critically ill population. METHODS: Researchers conducted a retrospective case-control study with a main and validation analysis. Data were extracted from the New York Statewide Planning and Research Cooperative System. For the main analysis, there were 415 cases with a hospital-acquired pressure injury (HAPI) and 194, 872 controls without. Researchers then randomly selected 100 cases with a HAPIs and 300 controls without for the validation analysis. A step-up logistic regression model was used. Researchers generated receiver operating characteristic curves for both the main and validation analyses, assessing the overall utility of the regression model. RESULTS: Eleven variables were significantly and independently related to ASF: renal failure (odds ratio [OR], 1.4, P = .003), respiratory failure (OR, 2.2; P = < .001), arterial disease (OR, 2.4; P = .001), impaired nutrition (OR, 2.3; P = < .001), sepsis (OR, 2.2; P = < .001), septic shock (OR, 2.3; P = < .001), mechanical ventilation (OR, 2.5; P = < .001), vascular surgery (OR, 2.2; P = .02), orthopedic surgery (OR, 3.4; P = < .001), peripheral necrosis (OR, 2.5; P = .003), and general surgery (OR, 3.8; P = < .001). The areas under the curve for the main and validation analyses were 0.864 and 0.861, respectively. CONCLUSIONS: The final model supports previous work and is consistent with the current definition of ASF in the setting of critical illness.